MAKANAN DAN MINUMAN DALAM PERSPEKTIF HUKUM ISLAM - Huzaemah Tahido Yanggo (TAHKIM, 2013)
Humans have several primary needs. One of the primary needs of human is food and beverages. In Islamic teaching, food and beverages consumed by humans, especially Muslims should be selective, that is permitted (halal) according to instructions of Allah in the Qur'an and explanation the Prophet of Muhammad in the hadith, as well as thayyiban in quality, ie. the foods useful to the body, not damage, not disgusting, awful, is not expired and not contrary to Allah instruction, because it is not forbidden. The Islamic law through al-Quran and Hadith has established some kind of food and beverages which prohibited to consume by Muslims, among others, carrion, blood, pork, animals slaughtered in the name of other than Allah, as well as the wine and all kinds of intoxicants beverages.The food and drinks are forbidden because threatens the human life, contrary to the maintenance of life (hifz al-nafs), maintenance of intellect (hifz al-'aql) and maintenance of property (hifz al-mal) in maqasid al-Shari'ah. Keywords: food, beverages, Islamic law